2019
DOI: 10.5194/aab-62-205-2019
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced changes in skin temperature and blood parameters in horses

Abstract: The aim of the study was to assess the effects of training on haematological and biochemical blood parameters as well as on the changes in body surface temperature in horses. In order to identify the predictive value of surface temperature measurements as a marker of animal's performance, their correlations with blood parameters were investigated. The study was carried out on nine horses divided into two groups: routinely ridden and never ridden. Infrared thermography was used to assess surface temperature cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 23 publications
6
49
2
1
Order By: Relevance
“…However, the authors did not investigate LAC. Soroko et al [21] used a treadmill in their study, but the biomechanical differences between exercise on a treadmill and a racetrack should be emphasized [2,34]. On the treadmill, the length of the gait is longer than for overground conditions [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors did not investigate LAC. Soroko et al [21] used a treadmill in their study, but the biomechanical differences between exercise on a treadmill and a racetrack should be emphasized [2,34]. On the treadmill, the length of the gait is longer than for overground conditions [2].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the highest increase in T Max, T Min, and T Aver occurred in ROIs 9-11 (m. latissimus dorsi, m. obliquus externus abdominis, and m. pectoralis transversus regions) immediately after exercise, possibly as a consequence of the most loaded muscle during that type of exercise. The most recent work assessed the effects of training on hematological and biochemical blood parameters [33], as well as on the changes in body surface temperature in horses [21]. The authors indicated a significantly higher surface temperature in neck, back, gluteal, and quarter muscles after training, connected with the dynamics of changes in HCT, CPK, and, urea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in superficial temperatures may be caused by a combination of physical activity and physiological stress responses [15,29,30], which is not easy to differentiate. Interestingly, infrared thermography has been used to identify physiological stress in horses based on the evaluation of eye temperature [31], which showed positive correlations with heart rate, heart rate variability, stress related behaviors, and cortisol concentration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Como es de conocimiento, el caballo peruano de paso no es usado exclusivamente para el trabajo, sino más bien para exhibiciones y concursos. Durante el tiempo previo a dichos eventos, los caballos son sometidos a entrenamientos durante largos periodos; pudiendo denotar cambios hematológicos y bioquímicos en relación con aquellos que no son forzados a estas prácticas y ejercicios intensos (30,31,32). Esto pudiera ser un factor condicionante, de cambios en los valores hematológicos en el Caballo Peruano de Paso.…”
Section: Discussionunclassified